Antidiabetic Activities and Identification of Chemical Compound from Samama (Anthocephalus macrophyllus (Roxb) Havil) - Laela Nur Anisah; Wasrin Syafii; Gustan Pari; Rita Kartika Sari (Universitas Gadjah Mada, 2018)
Samama (Anthocephalus macrophyllus) is one of a pioneer indigenous fast growing species in Indonesia which have been used as traditional medicine for various diseases. The objectives were to determine the yield extract, to analyze their antidiabetic activity by inhibition assay for α-glucosidase enzyme activity and chemical analysis with GCMS. Extraction of leaves, bark and wood samples were done by using ethanol 95%. Fractionation the most active ethanol extract was conducted by using n-hexane and ethyl acetate. The yield of ethanol extracts in leaves, bark and wood were 13.90%, 12.87%, and 2.18% respectively. Based on antidiabetic activity assay, the bark ethanol extract was the most active extract by the IC50 value of 5.86 μg mL-1. Phytochemical analysis on bark ethanol extracts showed that they contained flavonoid, quinon, triterpenoid, saponin and tannin which were assumed have high contribution in antidiabetic activities. The result of fractionation ethanol extract bark showed that the ethyl acetate fraction was the most active fraction (IC50 6.82 μg mL-1). GCMS analysis indicated the presence of dominant phenolic compounds such as pyrocatechol, antiarol, isopropyl myristate and phenol in which were suspected have antidiabetic activity. These results strongly suggested that ethyl acetate fraction of Samama bark was a potential natural source for antidiabetic agents.